Probationary Confidence Value Mechanism for Trust-Based Autonomous Routing in MANETs with Sequence Number Validation - Kute V. B.; Nichat M. K.; Sagane S. S.; Nemade P. G.; Choudhary S. R.; Chhajed K. K. (EPJ Web of Conferences)
Multi-hop routing, Self-configuring, infrastructure-less Mobile Ad Hoc Networks (MANETs), are vulnerable to various attacks. Ad-hoc on-demand multipath distance vector (AOMDV) routing protocol has been one of the prevalent choices to overcome the network reliability challenges. The AOMDV becomes more useful as it has a mechanism to discover multiple paths of non-overlapping nature. AOMDV appears to be vulnerable to sequence number attacks due to its route discovery procedure. The rogue node/s modifies the sequence numbers in routing messages. This manipulation may cause wrong or incorrect routing. This work targets to present mechanism to prevent the attack on AOMDV happening due to manipulations of sequence number. The proposed method mitigates the attack's impact through a combination of sequence number validation, anomaly detection, and reputation-based routing. Through the experimental results the paper demonstrates the comparison of the proposed solution with existing system with the help of packet delivery ratio (PDR), end-to-end delay, and throughput.